2019
DOI: 10.3354/ab00710
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature and sex steroids on sex ratio, growth, and growth-related gene expression in the Chinese giant salamander Andrias davidianus

Abstract: Andrias davidianus is one of most farmed amphibians owing to its palatability and nutritional value. In this transitional group between aquatic and terrestrial animals the effects of temperature and sex hormones on sex ratio and growth are not fully understood. Here, we quantified the sex dimorphism of A. davidianus growth with adult males approximately 30% larger than females, and for the first time determined the time of initiation of sex differentiation to be ~98 days post-hatching (dph). Mortality increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…According to laboratory studies, A. davidianus larvae are sensitive to temperature variations [ 37 , 38 ]. The optimal growth occurs in water with a temperature range of 15–21 °C [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…According to laboratory studies, A. davidianus larvae are sensitive to temperature variations [ 37 , 38 ]. The optimal growth occurs in water with a temperature range of 15–21 °C [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…2013001). According to previous study, we found that gonad of A. davidianus began to differentiate on the 98 days after fertilization (Hu et al, 2019a). The developing stage gonads of 62 dpf (days post fertilization), 98 dpf, 130 dpf and 1-, 2-, 3-, 4-, 5-, and 6-years-old (6 years old) giant salamanders in the normal group and sex hormone induction group were collected.…”
Section: Tissue Collectionmentioning
confidence: 99%
“…At 5 h postchallenge with S. agalactiae as previously described (35), spleen tissue was collected from 15 resistant and 15 susceptible fish. Each sample was divided into three parts, one preserved in RNALater (Applied Biosystems, Foster City, CA) and stored at 270˚C for RNA extraction, the second fixed in 4% paraformaldehyde (pH 7.5) for 24 h and stored in 70% ethanol to detect the differences in microstructure by histology according to the described method (36), and a third preserved in ethanol for DNA extraction. Spleens of Nile tilapia with no pathogen exposure were collected and fixed in 4% paraformaldehyde (pH 7.5) as control.…”
Section: Fish and Sample Preparationmentioning
confidence: 99%
“…The cytosine methylation levels were determined according to the uniquely mapped reads, as previously described (39). The library construction and RNA-seq were as described (36).…”
Section: Library Construction and Sequencingmentioning
confidence: 99%